2016
DOI: 10.1002/ptr.5708
|View full text |Cite
|
Sign up to set email alerts
|

Decursin in Angelica gigas Nakai (AGN) Enhances Doxorubicin Chemosensitivity in NCI/ADR‐RES Ovarian Cancer Cells via Inhibition of P‐glycoprotein Expression

Abstract: Angelica gigas Nakai (AGN, Korean Dang-gui) is traditionally used for the treatment of various diseases including cancer. Here, we investigated multidrug-resistant phenotype-reversal activities of AGN and its compounds (decursin, ferulic acid, and nodakenin) in doxorubicin-resistant NCI/ADR-RES ovarian cancer cells. Our results showed that a combination of doxorubicin with either AGN or decursin inhibited a proliferation of NCI/ADR-RES cells. These combinations increased the number of cells at sub-G1 phase whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 35 publications
0
25
0
Order By: Relevance
“…Recently, drugs derived from the medicinal herb are popular around the world and have become a hot area of research. Decursin, a major compound isolated from the root of the Korean Dang‐gui ( Angelica gigas Nakai, AGN), was used to treat various diseases, which shows activities of antiliver fibrosis (Y. J. Choi et al, ), anticancer (J. H. Kim, Jung, Kim, & Jeong, ; J. M. Kim et al, ; W. J. Kim, Lee, Choi, & Moon, ), and anticancer therapy sensitization (H. S. Choi et al, ; J. Kim et al, ). Most importantly, previous study also indicated that decursin shows low cytotoxicity to normal tissue as a cancer‐targeted therapy agent (Lee et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, drugs derived from the medicinal herb are popular around the world and have become a hot area of research. Decursin, a major compound isolated from the root of the Korean Dang‐gui ( Angelica gigas Nakai, AGN), was used to treat various diseases, which shows activities of antiliver fibrosis (Y. J. Choi et al, ), anticancer (J. H. Kim, Jung, Kim, & Jeong, ; J. M. Kim et al, ; W. J. Kim, Lee, Choi, & Moon, ), and anticancer therapy sensitization (H. S. Choi et al, ; J. Kim et al, ). Most importantly, previous study also indicated that decursin shows low cytotoxicity to normal tissue as a cancer‐targeted therapy agent (Lee et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…For example, gambogenic acid has been reported to increase the chemosensitivity of breast cancer cells to ADR via suppressing the PTEN/PI3K/AKT pathway (10). Meanwhile, Choi et al revealed that decursin found in Angelica gigas Nakai (AGN) could inhibit the proliferation of ADR-resistant ovarian cancer cells and induce apoptosis in the presence of ADR via blocking P-glycoprotein expression (11).…”
Section: Introductionmentioning
confidence: 99%
“…The antiproliferation potentials of AGN/RSV NPs were evaluated in SKOV-3 cells by a colorimetric assay ( Figure 6 and Table 2 ). The anticancer activities of ingredients and extracts of AGN against ovarian cancer cells were already reported somewhere [ 20 ]. In our previous report [ 24 ], the antiproliferation efficiency of AGN nanoformulation in breast cancer cells (that is, MCF-7 cells) was demonstrated.…”
Section: Resultsmentioning
confidence: 99%
“…Among diverse phytomedicines for cancer prevention and therapy [ 16 , 17 , 18 ], the pharmacological effects of single components and extracts of Angelica gigas Nakai (AGN) have been widely investigated [ 19 ]. The main components of AGN, such as decursin (D) and decursinol angelate (DA), and its extracts have anticancer potentials in several types of cancers, such as breast, blood, cervical, colon, lung, oral, ovarian, prostate, and skin cancers [ 20 , 21 , 22 , 23 , 24 , 25 , 26 ]. In our previous studies [ 22 , 24 , 26 ], AGN extract and AGN particles have shown anticancer activities in breast, buccal, and cervical cancers.…”
Section: Introductionmentioning
confidence: 99%